Improving the Knock-Out Properties of Moulding Sands with an Inorganic Binder - J. Jakubski; D. Halejcio (Archives of Foundry Engineering)
Moulding sands with an inorganic binder are mainly used in non-ferrous metal casting employed in the automotive industry. The disqualifying factor for their use in iron alloy casting is their high final strength, associated with further solidification of the water glass as the temperature rises. The subject addressed in this study aims to improve the knockout properties of moulding sands with water glass. In this case, a foundry sand additive of geological origin was used. This additive is a reclaimed waste from the construction industry. The moulding sand was made with a binder, which was water glass R145 (3.5 parts by weight), and as a hardener, Flodur 1 was used in a ratio of 5% to the binder and additionally, 2 and 3 parts by weight of an additive with grain sizes of 0.2mm, 0.16mm, and 0.10mm were used. Research was conducted on the impact of strength on bending and stretching, as well as permeability. Subsequently, a test was carried out in accordance with the Polish standard PN-85/H11005 by pouring the mould with liquid metal. It was demonstrated that the investigated additive does not have a negative impact on bending strength and permeability values and reduces the amount of work required to remove the core from the cast iron casting.